New Therapies and Immunological Findings in Melanoma and Other Skin Cancers - Atsushi Otsuka (Frontiers Research Topics, 2019)
New therapies are currently being developed in the field of skin cancer. In particular, advances in melanoma now represent the frontline of cancer immunotherapy, as immunological findings in the disease have led to the development of highly effective immune-checkpoint inhibitors. However, these immune-checkpoint inhibitors are only effective in a subset of patients, and may not work in other skin cancer types, thus highlighting the need for further innovation in the field of skin cancer treatment. The purpose of this Research Topic is therefore to provide an up-to-date overview of immune processes and new therapies for melanoma and other skin cancers in order to further stimulate the development of new and even more successful treatments.